A cell-based, SARS-CoV-2 spike protein interaction assay to inform the neutralising capacity of recombinant and patient sera antibodies - Harrison, Neale; Richardson, Lauren; Pallini, Chiara; Morano, Ines; Jinks, Elizabeth; Cowley, Jamie; Chan, Hujo; Hill, Harriet J.; Tuekprakhon, Aekkachai; Li, Zhi; Matas de las Heras, Cristina; Teodosio, Ana; et al. (Frontiers in Virology, 2023)
The engagement of the SARS-CoV-2 spike protein with ACE2 is a critical step for viral entry to human cells and accordingly blocking this interaction is a major determinant of the efficacy of monoclonal antibody therapeutics and vaccine-elicited serum antibodies. The emergence of SARS-CoV-2 variants necessitates the development of adaptable assays that can be applied to assess the effectiveness of antibody-based therapeutics. Through testing of a range of recombinant spike proteins, we have developed a cell based, ACE2/spike protein interaction assay that characterises monoclonal anti-spike protein antibodies and neutralising antibodies in donor serum. The assay uses high-content imaging to quantify cell bound spike protein fluorescence. Using spike proteins from the original ‘Wuhan’ SARS-CoV-2 virus, as well as the delta and omicron variants, we identify differential blocking activity of three monoclonal antibodies directed against the spike receptor binding domain. Importantly, biological activity in the spike interaction assay translated to efficacy in a SARS-CoV-2 infection assay. Hence, the spike interaction assay has utility to monitor anti-spike antibodies against the major known SARS-CoV-2 variants and is readily adaptable to quantify impact of antibodies against new and emerging SARS-CoV-2 variants.